The interaction between teacher-student and student-student in the face of conflicts in a classroom of an educational institution of initial level of Pueblo Libre - Pure Chaupis, María Fernanda (2022)
The general objective of this study was to analyze the interactions between teacher-student and student-student in the face of conflicts. The research design was ethnographic. The population studied consisted of 17 students, a teacher and an assistant / mother, belonging to an initial level educational institution of Pueblo Libre. The categories studied were five: types of conflict, causes of conflict, perceptions of conflicts, teacher-student interaction: teacher action, and child interaction. The instruments applied were the observation guide and the interview guide. Among the most outstanding findings, it can be affirmed that the interactions occurred from various causes and types, and that the attitudes and strategies of the teacher and students did not interfere with the resolution of the evidenced conflicts.